The contribution of professor Irynarkh Shchogolіv (1873–1943) in the development of Ukrainian scientifi c natural terminology - Onyshchenko, Anastasia (Ukrainian Peasant, 2021)
Introduction. On the way to European integration, issues of Ukrainian scientifi c terminology remain important and relevant. The approval of new innovative developments, the development of educational concepts and the popularization of the achievements of domestic science depend on its clarity and unambiguity. Scientifi c interest is to study the historical progress of the enrichment of the Ukrainian scientifi c language as a means of developing national science and education in the context of studying the heritage of outstanding agricultural scientists. Purpose of the article is to investigate the contribution of Professor Irynarh M. Shchogoliv (1873–1943) to the development of Ukrainian scientifi c natural terminology. Methods. The methodology is based on the general scientifi c principles of historical knowledge: historicism, objectivity, systematization, complexity, scientifi city, multifactoriality and comprehensiveness. In addition, important importance is attached to the use of general scientifi c methods (analysis, synthesis, generalization), interdisciplinary (statistical, bibliographic) and historical (problem-chronological, descriptive, historical-systemic, comparative-historical, periodization, personalization). Methods of source and archival analysis are also involved in the research process. Results. The fi rst organizational attempts to systematize terminological work in the Ukrainian lands took place after the political thaw of 1905. Archival research has shown that during I. Shchogoliv’s studies at the agricultural department of the Kyiv Polytechnic Institute in 1906–1910, scientifi c circles played an important role in attracting students to the community work and deepening of the acquired knowledge. In 1906, student I. Shchogoliv became a secretary (clerk) of the «Circle of Naturalists» under the leadership of O. Yanata. The greatest scientifi c interest is the activity of the Ukrainian Terminological Commission, established in 1910 with the participation of S. Veselovsky, I. Shchogoliv and O. Yanata. We have found out that I. Shchogoliv took part in expeditions to select and systematize the terminological material from printed sources and collect folk names that remained unnoticed. I. Shchogoliv was involved in a project to study the nature of Ukraine as part of a special Commission for Regional Studies of «Circle of Naturalists». In addition, he served as its secretary. During the Ukrainian revolution, Professor I. Shchogoliv worked in the Ukrainian Scientifi c Society as a member of the natural and agronomic sections. He systematized the materials for the dictionary of zoological terminology. In 1918, I. Shchogoliv’s «Dictionary of Ukrainian Entomological Nomenclature» was published. In 1927, two parts of the «Dictionary of Zoological Nomenclature» were edited by the zoological section of the Natural Sciences Department of the Institute of Ukrainian Scientifi c Language of the Ukrainian Academy of Sciences, and in 1928 – the third part – «Names of Invertebrates» by Professor I. Shchogoliv and S. Panochini. In addition, Professor I. Shchogoliv edited manuscripts of various scientifi c works and textbooks in terms of terminology and scientifi c language. Originality. We have investigated Shchogoliv’s heritage in natural terminology for the fi rst time in historical science. The source base of the study covers a wide range of published and unpublished materials, archival documents and scientists’ scientifi c works. His research activity in this fi eld was during 1909–1929 in the «Circle of Naturalists» of the Kyiv Polytechnic Institute; the Ukrainian Scientifi c Society; the Institute of the Ukrainian Scientifi c Language of the All-Ukrainian Academy of Sciences. We have proved his priority in the development of zoological nomenclature. Conclusions. The study of scientifi c heritage of the outstanding scientist-entomologist, teacher, professor I. Shchogoliv allowed to open a new milestone of his work: participation in the development of Ukrainian scientifi c natural terminology. While still a student, he joined the terminology deed, managed to organize like-minded people and organize the acquired knowledge in terminological and nomenclature dictionaries, which have not lost their signifi cance to this day. The achievements of the scientist in the formation of a fullfl edged professional nomenclature is a valuable source for studying the historical progress of domestic natural science. Research on the achievements of predecessors in the fi eld of term formation is timely, because in the light of the new law on language, all branches of science and technology need systematic terminological work in order to take its rightful place on the world stage.